Formation of Discipline Character Through Internalization of the Value of Islamic Religious Education in the Students of the Wali Songo Ngabar Islamic Boarding School - Said, Ghiffari Syauqy; Ridwan, Muhtadi; Sholeh, Ahmad (FONDATIA, 2025)
Amid growing concern over the decline of character education among Indonesia’s youth, particularly in relation to student discipline, Islamic boarding schools (pesantren) have emerged as vital institutions for cultivating moral integrity through continuous and holistic educational practices. This study investigates the development of student discipline through the internalization of Islamic educational values at the Wali Songo Islamic Boarding School in Ngabar Ponorogo. Employing a qualitative case study design, data were gathered through non-participant observation, in-depth interviews with educators and students, document analysis, and field notes. The study identifies three primary strategies contributing to the internalization process: role modeling by educators, habituation via structured daily routines, and firm yet constructive rule enforcement. The internalization of discipline unfolds through the phases of value transformation, transaction, and trans-internalization, embedding the core Islamic principles of iman (faith), sharia (Islamic law), and akhlaq (morality) into students’ behavior. Discipline, as developed in this context, transcends mere obedience and is manifested as intrinsic moral awareness that shapes students’ conduct within and beyond the school environment. Although challenges persist, particularly among senior students, sustained mentoring and institutional consistency significantly mitigate disciplinary issues. The findings suggest that formal educational institutions may benefit from adopting key elements of the pesantren model, particularly the integration of moral exemplars, routine-based learning, and value-oriented discipline, to enhance character formation in contemporary schooling.